Storable good monopoly: The role of commitment - Paolo Dudine; Igal Hendel; Alessandro Lizzeri (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
We study dynamic monopoly pricing of storable goods in an environment where demand changes over time. The literature on durables has focused on incentives to delay purchases. Our analysis focuses on a different intertemporal demand incentive. The key force on the consumer side is advance purchases or stockpiling. In the case of storable goods the stockpiling motive has been documented in recent empirical literature. Advance purchases can also arise in the case of durables, although the literature has not focused on this case. We show that if the monopolist cannot commit, then prices are higher in all periods, and social welfare is lower, than in the case in which the monopolist can commit. This is in contrast with the analysis in the literature on the Coase conjecture.
Keywords: 330